ACG Clinical Guideline: Diagnosis and Management of Pancreatic Cysts. (April 2018) - Elta, Grace H; Enestvedt, Brintha K; Sauer, Bryan G; Lennon, Anne Marie
Abstract : N/A: Pancreatic cysts are very common with the majority incidentally identified. There are several types of pancreatic cysts; some types can contain cancer or have malignant potential, whereas others are benign. However, even the types of cysts with malignant potential rarely progress to cancer. At the present time, the only viable treatment for pancreatic cysts is surgical excision, which is associated with a high morbidity and occasional mortality. The small risk of malignant transformation, the high risks of surgical treatment, and the lack of high‐quality prospective studies have led to contradictory recommendations for their immediate management and for their surveillance. This guideline will provide a practical approach to pancreatic cyst management and recommendations for cyst surveillance for the general gastroenterologist.